Scheduling a Project to Maximize Its Present Value: A Zero-One Programming Approach - Doersch, Robert H.; Patterson, James H. (Management Science, 1977)
A zero-one integer programming formulation of the project scheduling problem is reported which maximizes the discounted value of cash flows in a project when progress payments and cash outflows are made upon the completion of certain activities. While this problem has been treated previously, it has not been addressed in a manner which allows for the type of constraints treated in this paper. And while cash can be treated as any other resource in the noncash flow, resource-constrained version of this problem, the effects of cash inflows and outflows and the time sequencing alternatives for them allow for a different treatment of cash resources than has been previously reported.